Corrigendum on "Solubility determination and modelling for phthalimide in mixed solvents of (acetone, ethyl acetate or acetonitrile + methanol) from (278.15 to 313.15) K" [J. Chem. Thermodyn. 106 (2017) 123–131]. (October 2017) - Shi, Hongwei; Du, Cunbin
Abstract: Combined Nearly Ideal Binary Solvent/Redlich-Kister (CNIBS/R-K) equations reported by our group (J. Chem. Thermodyn. 106 (2017) 123–131) for calculating the solubility of phthalimide in mixed solvents of (acetone, ethyl acetate or acetonitrile + methanol) at various temperatures. The numerical values of the curve-fit equation coefficients do not provide a satisfactory representation of the mole fraction solubility of phthalimide in (acetonitrile + methanol) binary mixtures. The values of the correlation parameters for the CNIBS/R-K model were recalculated.